Perceptions of stakeholders in English language learning: a case study - Day, Leah K., author; Ginsberg, Ricki, advisor; Nekrasova-Beker, Tatiana, committee member; Basile, Vincent, committee member (Colorado State University. Libraries, 2023)
This study was conducted as a qualitative narrative inquiry. The purpose of the study was to understand the perceptions of stakeholders on English Language Learners and how this shapes their educational path. By using a qualitative narrative inquiry, we can get a closer look into the life and learning of just one specific student. Data was collected in the form of interviews with the participants. The interviews were guided with a set of questions that were designed to interrogate perceptions and experiences of all stakeholders with regards to language learning in the context of one student. With the exception of WIDA scores that provide information about the language mastery level of the student, all data collected was qualitative. Interviews were recorded and transcribed and the data was coded inductively. This was then compiled in the form of a narrative that described the shaping of the educational pathway of the student. This study does not seek to generalize beyond this context but can provide insight into similar experiences and perceptions of the English Language Learning process. The themes that developed as findings of this study were centered around the disconnects between stakeholders. This presented itself as subthemes like lack of teacher understanding, feelings of isolation, perceptions of English Language Learners, and varying teacher perceptions of their language abilities. There are implications in the teaching of English Language Learners that point to the importance of collaboration between all stakeholders. This includes transparency and clarification of educator roles, parent outreach, and professional development.
Keywords: educators; perceptions; collaboration; stakeholders; language learning